International democracy assistance for peacebuilding Cambodia and beyond - Peou, Sorpong (Rethinking peace and conflict studies, 2007)
This book explains why international donors may succeed in putting war-torn countries on the path of democratic transition and negative peace, but fail to consolidate the gains they make. Critical of neo-institutionalism, but sympathetic to historical and normative institutionalism, this book advances 'complex realist institutionalism' theory.